RELATIOSHIP MARKETING IN BRAZILIAN MICRO (CIPEEX, 2022)
GIVEN THE CONTINUOUS AND ACCELERATED CHANGES SEEN IN THE FIELD OF BUSINESS, ESPECIALLY ON THE COVID-19 PANDEMIC, MICRO AND SMALL COMPANIES WERE FORCED TO IMPLEMENT NEW STRATEGIES TO FACE THE MARKETBARRIERS, CONQUERING AND RETAINING THEIR AUDIENCE. RELATIONSHIP MARKETING CONTRIBUTES TO OPTIMIZING THEBONDING WITH THE CLIENT OF THESE COMPANIES, ADDING STRATEGIC VALUE TO MANAGEMENT DECISION-MAKINGPROCESSES. IN THIS SENSE, WE SEEK TO ANALYZE HOW RELATIONSHIP MARKETING CAN BE USED IN MICRO ANDSMALL BRAZILIAN COMPANIES. SPECIFICALLY, IT WAS SOUGHT TO CONCEPTUALIZE AND DEFINE MARKETING;UNDERSTAND HOW RELATIONSHIP MARKETING HELPS TO FACING THE CURRENT MARKET CHANGES AND HIGHLIGHT THEIMPORTANCE OF THE RELATIONSHIP TO ATTRACT, CONQUER AND RETAIN COSTUMERS. A BIBLIOGRAPHIC RESEARCH WASDEVELOPED, THUS PRESENTING A LITERATURE REVIEW. DATA FROM 26 PUBLICATIONS OF PHYSICAL BOOKS ANDSCIENTIFIC ARTICLES EXTRACTED FROM THE ELECTRONIC DATABASE OF GOOGLE SCHOLAR AND SCIELO WERE ANALYZED.THE RESULTS FOUND SHOWED THAT RELATIONSHIP MARKETING HAS BEEN CONSIDERED A STRATEGIC MANAGEMENTTOOL, WHICH TENDS TO FACILITATE DECISION-MAKING PROCESSES IN MICRO AND SMALL COMPANIES OPERATING INBRAZIL. IN THIS ASPECT, IT WAS CONCLUDED THAT RELATIONSHIP MARKETING FAVORS THE CONSTRUCTION ANDSTRENGTHENING OF TIES ESTABLISHED WITH THE CLIENT, ALLOWING GREATER ATTRACTIVENESS FOR THEIR CONQUEST ANDLOYALTY, HELPING TO MAINTAIN A GOOD MARKET POSITIONING AND CONTRIBUTING TO THE DEVELOPMENT AND GROWTHOF MICRO AND SMALL COMPANIES.
Keywords: Relationship Marketing; Costumers; Conquer; Retain.